Seroprevalence of Hepatitis C Virus in Opioid User Patients (International Journal of Food and Nutritional Sciences, 2022)
Background- Hepatitis C Virus (HCV) infection is a major public health problem worldwide and remain a vital cause of chronic hepatitis. We characterized HCV antibody prevalence among opioid user patients in district Hospital, Hanumangarh, Rajasthan. Opioid users are categorized in high risk group for occurrence of HCV due to use of injectable equipment, sharing of equipments like pipes, inhaler etc.Method- A cross sectional study based on demographic and behavioral characteristics were obtained by a standardized questionnaire. Serum samples were tested for HCV using Enzyme Linked Immuosorbant Assay.Result- A total of 852 opioid users were examined and tested for anti –HCV by serological Enzyme Linked Immunosorbant Assay. Among opioid users 20.3% (173) were injectable opioid users and 79.7% (679) were non injectable opioid users. The prevalence of HCV in injectable drug users were found to be high with 27.8% (48/173) than Non injectable drug users with 3.4% (23/679). The overall prevalence of opioid users is found to be 8.3% (71/852).Conclusion- Our study shows high prevalence in Injectable DrugUsers. The study helps us to evaluate various aspects associated with Hepatitis C Infection. The need of hour is to increase the awareness about Hepatitis C Virus among the public and practicing physicians.